Organizational Culture and Masculinities in a Startup Company in Finland - Pöllänen, Katri (Nordic Journal of Working Life Studies, 2021)
This article explores the organizational culture of the startup scene in Finland. Startup companies offer an interesting setting for research, because their organizational culture, hierarchy and power structures differ from those of large traditional organizations. The method used in this study was an organizational ethnography in a startup company in Finland, which included participant observation, and interviews with employees. The organizational culture of the startup was informal, relaxed, low in hierarchy, and employees had autonomy for deciding on their working times and locations. Masculinities were visible in the organizational culture of the startup company in the form of ‘harsh’ language and rambunctious humor, men changing their behavior and discussion topics when women were around, and managers communicating more aggressively with men than with women. The results further showed that gender was a criterion for inclusion and exclusion. The research concludes that startup companies are not gender-neutral spaces.